Selectivity descriptors for the direct hydrogenation of CO2 to hydrocarbons during zeolite-mediated bifunctional catalysis - Ramirez, Adrian; Gong, Xuan; Caglayan, Mustafa; Nastase, Stefan-Adrian F.; Abou-Hamad, Edy; Gevers, Lieven; Cavallo, Luigi; Dutta Chowdhury, Abhishek; Gascon, Jorge (Nature communications, 2021)
Cascade processes are gaining momentum in heterogeneous catalysis. The combination of several catalytic solids within one reactor has shown great promise for the one-step valorization of C1-feedstocks. The combination of metal-based catalysts and zeolites in the gas phase hydrogenation of CO 2 leads to a large degree of product selectivity control, defined mainly by zeolites. However, a great deal of mechanistic understanding remains unclear: metal-based catalysts usually lead to complex product compositions that may result in unexpected zeolite reactivity. Here we present an in-depth multivariate analysis of the chemistry involved in eight different zeolite topologies when combined with a highly active Fe-based catalyst in the hydrogenation of CO 2 to olefins, aromatics, and paraffins. Solid-state NMR spectroscopy and computational analysis demonstrate that the hybrid nature of the active zeolite catalyst and its preferred CO 2 -derived reaction intermediates (CO/ester/ketone/hydrocarbons, i.e., inorganic-organic supramolecular reactive centers), along with 10 MR-zeolite topology, act as descriptors governing the ultimate product selectivity. The reaction mechanism of carbon dioxide to high-value hydrocarbons over metal-zeolite bifunctional catalysts remains ambiguous. Here, the authors demonstrate that active zeolite catalysts’ topology and hybrid nature are descriptors; regulating the reaction mechanism and ultimate product selectivity.